Gender in communication a critical introduction - Palczewski, Catherine Helen; McGeough, Danielle Dick; DeFrancisco, Victoria L. (Victoria Leto) (SAGE, 2023)
Gender in Communication: A Critical Introduction embraces the full range of diverse gender identities and expressions to explore how gender influences communication, as well as how communication shapes our concepts of gender for the individual and for society at large. Authors Catherine Helen Palczewski, Danielle D. McGeough, and Victoria Pruin DeFrancisco equip readers with the critical analysis tools to form their own conclusions about the ever changing processes of gender in communication. This comprehensive gender communication book is the first to extensively address the roles of religion, the gendered body, single-sex education, an institutional analysis of gender construction, social construction theory, and more. The Fourth Edition has streamlined the text to make it more accessible to students without sacrificing the sophistication of the book′s trademark intersectional approach. -- Provided by publisher.